Knowledge and precautions of light-curing composite resin restorations by dental students - Esthela Maria Pereira Castanheiro; Anna Carolina Cenci Matick Rombaldo; Júlia Calvo Nunes; Fernanda Midori Tsuzuki; Camila Hirata Navarro; Daniele Esteves Pepelascov; Raquel Sano Suga Terada (Editora Uningá, 2024)
Composite resin is versatile material for performing several dental procedures in dentistry, and its use has already been consolidated in this field. The clinical success of adhesive restorations is directly related to the knowledge of restorative material properties and light-curing unit factors, among others. The aim of the study was to assess the knowledge about the technical characteristics of light-curing devices and the forms of use and maintenance employed by undergraduate dental students. A total of 230 students answered a questionnaire containing six questions on technical data, use, and maintenance of light-curing units. Of the total number of participants, the majority were students from private educational institutions attending the last two years. With 59.1% of them unaware of the ideal irradiance of a light-curing unit, 73.0% were careful to position the light-curing unit as close as possible to the restoration, and 42.6% followed the light-curing time recommended by textbooks and theoretical texts. As for use and maintenance, 50.4% used the protector attached to the light-curing unit, 57.4% used safety barriers, and 63.0% sanitized the light tip after use. The evaluation suggests that student's knowledge of "light-curing resin materials" is incomplete. Therefore, it can be inferred that the students have a good understanding of biosafety precautions when using light-curing units, but more knowledge is needed about the technical and clinical aspects of the devices.